2021
DOI: 10.1002/jsfa.10963
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome‐metabolomic analyses of the impacts of dietary stachyose on fecal microbiota and metabolites in infants intestinal microbiota‐associated mice

Abstract: BACKGROUND: The intestinal microbiota and metabolites play an important role in human health and immunity. However, few studies have investigated the long-term effects of stachyose on the human intestinal microbiota and metabolism. Therefore, in this study, the feces of infants were transplanted into germ-free mice, and the effect of long-term stachyose intake on intestinal metabolism was examined by comparing the results of microbiome and metabolome analyses. Ultra-high-performance liquid chromatography-tande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…41 In animal models, stachyose has been associated with changes in the intestinal microbiome composition, a decreased inflammation of the intestine and an increased mucosal barrier function. [41][42][43][44][45] Stachyose has also been found to upregulate the production of the metabolite taurocholic acid, downregulate amino acid metabolism and significantly regulate the metabolism of taurine and hydroxytaurine, pantothenate and coenzyme A biosynthesis, as well as other signaling pathways. 45 It seems to be growth-promoting for Bifidobacteria.…”
Section: Discussionmentioning
confidence: 99%
“…41 In animal models, stachyose has been associated with changes in the intestinal microbiome composition, a decreased inflammation of the intestine and an increased mucosal barrier function. [41][42][43][44][45] Stachyose has also been found to upregulate the production of the metabolite taurocholic acid, downregulate amino acid metabolism and significantly regulate the metabolism of taurine and hydroxytaurine, pantothenate and coenzyme A biosynthesis, as well as other signaling pathways. 45 It seems to be growth-promoting for Bifidobacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The study showed that stachyose significantly altered the intestinal microbiota and metabolitescomposition, and increased the relative abundance of Verrucomicrobia, Actinobacteria, Akkermansia, and Bifidobacterium. [ 29 ] Other studies also show that stachyose promotes the growth of beneficial intestinal bacteria, inhibits pathogenic bacteria, and improves health outcomes in diabetes. [ 30 ]…”
Section: Discussionmentioning
confidence: 99%
“…These model systems present a powerful framework for integrating hypothesis testing into metabolomics studies of the microbiome and have been used to investigate diverse biological processes including aging 104 , reproduction 105,106 , and metabolism 13,14,16,107,108 . This strategy has been very successful in providing molecular insights into diverse diseases including colitis (both IBS and Crohn's disease) 15,17 , neurodegenerative disease 20,21 , breast cancer 32 , diabetes 109 , the biological response to toxin exposure 9,10,34,[110][111][112][113] , and the role that the microbiome plays in immunity 30,114 .…”
Section: Animal Model Strategies For Investigating Molecular Interact...mentioning
confidence: 99%